ANALISIS STATISTIK TEMPORAL ERUPSI GUNUNGAPI DI INDONESIA - , DESI KISWIRANTI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Indonesia was formed by the interaction of the three major tectonic plates. The tectonic plates are India-Australia plate, the Eurasian plate and the Pacific plate, so that almost 13% of volcanoes in the world (129 pieces of active volcanoes) located in the Indonesian archipelago. The volcanoes has the potential to cause natural disasters with the different intensity and power. Volcanic activity is a natural occurrence that is difficult to predict and may be considered as chaotic with no clear shape. Statistical methods can be applied to explain the pattern of volcanic eruptions as well as to help forecast future volcanic eruption activity. In this study, three temporal statistical methods applied are exponential distribution, Weibull distribution and Log-Logistic distribution. In general, the Log-Logistics distribution provides the highest probability of eruption that occurred within a specific time in the future with a 95% confidence level. Pattern of volcanic eruption in Indonesia are not normally distributed, so that the pattern of volcanic eruptions is a random. Qualitatively, the biggest eruption will follow the longest repose time interval. However, the magnitude of repose time no influence on the magnitude of VEI and doesnât affect to the probability of occurrence the volcanic eruptions in Indonesia. The average potential energy of the volcanic eruption in Indonesia period 1800-2012 amounted to 1,12587 x 1024 ergs and the average thermal energy of the volcanic eruption period 1800-2012 amounted to 1.29537 x 1024 ergs. Therefore, the total energy of the volcanic eruption in Indonesia amounted to 2,42124 x 1024 ergs.